(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Ximenia americana, a plant widely distributed in tropical and subtropical regions, has been traditionally used for various medicinal purposes. This paper critically analyzes the bioactive compounds present in Ximenia americana and evaluates its potential anti-cancer properties. The review encompasses the phytochemical composition of Ximenia americana, focusing on compounds such as ximenynic acid, lupeol, and β-sitosterol, among others, which have shown promising anti-cancer activities in preclinical studies.